Desain Sistem Gamifikasi Digital Berbasis Octalysis dan MDA Framework untuk Promosi Pariwisata Kota Surakarta - Agustina, Candra; Rahmawati, Eka; Permata, Afifta Ilham; Laily, Isnaini Mufidatul (Universitas Muhammadiyah Magelang, 2025)
Tourism plays a strategic role in driving local economic growth and preserving culture. However, the City of Surakarta still faces challenges such as the low length of stay of tourists and the lack of connectivity between destinations. This study aims to design a digital gamification strategy as an innovative approach to enhance the competitiveness of regional tourism. The research method used is mixed methods, combining qualitative and quantitative approaches. Data were collected through field observations, in-depth interviews with tourism stakeholders, surveys distributed to tourists, and trials of web- or mobile-based gamification applications. Qualitative data were analyzed using a thematic approach, while quantitative data were examined using descriptive and inferential statistics. The theoretical foundations applied are the Octalysis Framework and the MDA Framework (Mechanics–Dynamics–Aesthetics) to design game elements such as points, badges, challenges, and leaderboards in tourism promotion. The expected outcome is the development of a contextual and applicable digital gamification strategy model that can increase tourist engagement, extend the length of stay, and more evenly distribute economic benefits across the tourism ecosystem. This research contributes both academically and practically, serving as a guideline for local governments and tourism industry players to adopt interactive and sustainable digital strategies.